2011
DOI: 10.1016/j.foodres.2011.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Identification of polyphenolic compounds in red and white grape varieties grown in R. Macedonia and changes of their content during ripening

Abstract: The composition of polyphenols in the skin, seed and pulp extracts of the grapes of Vranec and Smederevka varieties, and Merlot and Chardonnay as well, was analyzed by liquid chromatography-diode array detectionmass spectrometry (HPLC-DAD-MS) and MS/MS techniques. Thirty-one phenolic compounds, including anthocyanins, flavonols and flavan-3-ols, as well as phenolic acids derivatives, have been identified in the extracts prepared from the grapes at physiological maturity, by mass spectrometry applying electrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
66
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 52 publications
(56 reference statements)
10
66
1
Order By: Relevance
“…One interesting result was that 'Red Globe' had less total phenolic compounds than 'Buca Razakısı' in all the treatments, except for the girdling alone. This is a result that conflicts with previous studies, which have reported that white varieties generally have fewer phenolic compounds than coloured varieties (Cantos et al, 2002;Lachman et al, 2004;Ivanova et al, 2011). This might have been the result of the 'Red Globe' vines being harvested before they had the chance to reach their "phenological maturity".…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…One interesting result was that 'Red Globe' had less total phenolic compounds than 'Buca Razakısı' in all the treatments, except for the girdling alone. This is a result that conflicts with previous studies, which have reported that white varieties generally have fewer phenolic compounds than coloured varieties (Cantos et al, 2002;Lachman et al, 2004;Ivanova et al, 2011). This might have been the result of the 'Red Globe' vines being harvested before they had the chance to reach their "phenological maturity".…”
Section: Resultscontrasting
confidence: 69%
“…The coloured varieties, 'Alphonse L.', 'Red Globe' and 'Trakya Ilkeren', contained more phenolics in their berries, as expected, compared to 'Buca Razakısı', the white cultivar. Coloured grape cultivars accumulate more anthocyanins in the skin and has the highest total polyphenols (Ivanova et al, 2011). One interesting result was that 'Red Globe' had less total phenolic compounds than 'Buca Razakısı' in all the treatments, except for the girdling alone.…”
Section: Resultsmentioning
confidence: 94%
“…The formation of color in grapes generally takes place during the veraison period with the biosynthesis of phenolic compounds (Ivanova et al, 2011;Kalkan Yildirim, 2006). In wine, color develops by the extraction of phenolic compounds in the grape during crushing, maceration and fermentation, and evolves through oxidation and aging (Gó mez-Míguez et al, 2007;Ivanova et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As expected, no anthocyanins were determined in the flours obtained from 'Italian Riesling', because white cultivars lack the UFGT expression, a gene involved in anthocyanins synthesis (Boss et al, 1996). Also, as support to these results, other studies reported the lack of anthocyanins in white grapes (Kammerer et al, 2004;Ivanova et al, 2011). On the other hand, this analytical was 535 performed by taking into account the early discovery of the occurrence of anthocyanins in white berries of Muscat Gordo Blanco cultivar (Gholami and Coombe, 1995).…”
Section: Total Anthocyanins Content (Tac)mentioning
confidence: 57%